EFFECT OF FIRM CHARACTERISTICS ON CAPITAL STRUCTURE OF DEPOSIT MONEY BANKS LISTED ON NIGERIAN STOCK EXCHANGE (Journal of Global Accounting, 2023)
The main aim of this study is to find out the effect of firm characteristics on capital structure of Deposit Money Banks listed on Nigerian Stock Exchange (NSE) as at December, 2017. Specifically, it investigated the extent to which firm size and asset tangibility affects debt-to-capital ratio and debt-to-asset ratio of Deposit Money Banks. In pursuit of the objective of this study, hypotheses were formulated and tested using secondary data obtained from the firms’ annual report and fact book. The ex-post facto design was adopted in carrying out this research. Data were analyzed using Pearson correlation analysis and multiple regression analysis with aid of E-view 9.0 which was to ascertain the direction and strength of the relationship between the variables of the study. The findings of this study confirm that the hypotheses tested were significant at 5% level of significance. Therefore, the researcher recommends that management of Deposit Money Banks need to embrace innovation as a way of increasing the efficiency of the assets and they should strive to attain a sound asset base in order to meet, on a timely basis, their responsibilities towards the customers and by extension, improve on their capital base; especially in the long term.
Keywords: Firm Size, Asset Tangibility; Debt-to-Capital Ratio; Debt-to-Asset Ratio.